Przypadek rynku wartości negatywnych - Stańczyk, Elżbieta; Stańczyk, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The article contains suggestions of the analysis of the relation: fertility to law regulations which are written in language of negative value economics. The basic language which is used to describe the demography and the fertility processes is the economic language. The transformation from traditional nations to industry ones has made a change in the perception of the worth of a child. The way of economy of such a peculiar good as a child is the subject of government’s interesting in shape of definite law regulations. To describe these law regulations one can use the language of negative value economics.
Keywords: wartości negatywne; dziecko